LEARNING OBJECTIVES OF ISLAMIC RELIGIOUS EDUCATION IN SCHOOLS: THE ROLE OF THE TEACHER AND ITS IMPLICATIONS BASED ON RELEVANT STUDY - Naofa, Muhammad l; Zahari, Iqlima; Maq, Mumu Muzayyin; Sidik, Jafar; Kholik, Nur; Muhammad, Hasman Zhafiri (Dharmas Education Journal (DE_Journal), 2023)
The paper aims to determine the learning objectives of Islamic religious education in schools. The research design used is the literature review method. Literature study (literature review) is research carried out by researchers by collecting a number of books and magazines related to the problem and research objectives. This technique is carried out with the aim of uncovering various theories that are relevant to the problems being faced/researched as reference material in discussing research results. The results of this study are that religious education teachers are professional educators with the main task of educating, teaching, guiding, directing, training, modeling, assessing and distributing students." The role of the religious education teacher Islamic religious education is a conscious effort to prepare students to understand (know), be skilled at performing (doing) and practicing (becoming) the Islamic religion through educational activities. Of these three aspects, "the aspect of being (religious or living life based on Islamic teachings and values) is the main aim of Islamic religious education in schools. In other words, the most important thing about the process of Islamic religious education in schools is not the aim of making people who have mastered Islamic religious knowledge, religious experts, or are clever and skilled in implementing it, but the aim is to realize the values ​​of Islamic religious teachings in real life for students. , which is integrated into his everyday personality.